2010
DOI: 10.1038/nm.2108
|View full text |Cite
|
Sign up to set email alerts
|

Mosaic vaccines elicit CD8+ T lymphocyte responses that confer enhanced immune coverage of diverse HIV strains in monkeys

Abstract: An effective HIV vaccine must elicit immune responses that recognize genetically diverse viruses1, 2. It must generate CD8+ T lymphocytes that control HIV replication and CD4+ T lymphocytes that provide help for the generation and maintenance of both cellular and humoral immune responses against the virus3–5. Creating immunogens that can elicit cellular immune responses against the genetically varied circulating isolates of HIV presents an important challenge for creating an AIDS vaccine6, 7. Polyvalent mosaic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
179
0
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 212 publications
(188 citation statements)
references
References 18 publications
7
179
0
2
Order By: Relevance
“…In vivo experiments are, however, required to validate the approach for HCV. Experimental studies of mosaics in HIV-1 can be considered as proof of principle: mosaics can be synthesized and expressed and are immunogenic in animal models, and the total number and cross-reactivity of CD8 + and CD4 + T-cell responses are increased relative to natural and consensus antigens (Barouch et al, 2010;Kong et al, 2009;Santra et al, 2010). The T-cell mosaic antigen insert design could be used together with improvements in other areas of vaccine design.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In vivo experiments are, however, required to validate the approach for HCV. Experimental studies of mosaics in HIV-1 can be considered as proof of principle: mosaics can be synthesized and expressed and are immunogenic in animal models, and the total number and cross-reactivity of CD8 + and CD4 + T-cell responses are increased relative to natural and consensus antigens (Barouch et al, 2010;Kong et al, 2009;Santra et al, 2010). The T-cell mosaic antigen insert design could be used together with improvements in other areas of vaccine design.…”
Section: Discussionmentioning
confidence: 99%
“…Mosaic sets elicited multiple CD4 + and CD8 + responses, and the breadth of responses was many-fold higher than the responses to natural-strain antigens (Kong et al, 2009) when assayed using peptides that contain the most common epitope variants found in the sampled global diversity (Li et al, 2006). Similarly promising results were obtained in recently completed studies in macaques: HIV-1 mosaic antigens elicited responses with greater breadth (more responses to diverse variants overall) and greater depth (more variants recognized per response) than did natural strains (Barouch et al, 2010;Santra et al, 2010).…”
Section: Introductionmentioning
confidence: 94%
“…Polyvalent mosaic immunogens are generated from natural sequences via computational optimization so that they resemble natural proteins but systematically include common potential epitopes, providing diversity coverage comparable to that afforded by thousands of separate peptides. 111 Mosaic HIV-1 antigens delivered by replication-incompetent Ad26 vectors 112 or DNA prime-recombinant vaccinia boost regimens 113 have been shown to augment both the breadth and depth of antigen-specific T cell responses when compared with consensus or natural sequence HIV-1 antigens in RM. In RM, Ad/MVA (modified vaccinia Ankara) or Ad/Ad prime boost vectors expressing bivalent HIV-1 mosaic Env/Gag/Pol elicited neutralizing, and functional non-neutralizing Ab, robust T cell immune response and afforded significant reduction in the per-exposure acquisition risk following repetitive, intrarectal SHIV challenges.…”
Section: Mosaic Vaccinementioning
confidence: 99%
“…36 HIV-1 mosaic antigens have been shown to be processed and expressed by human T cells in vitro 37 and several proof-of-concept immunogenicity studies in non-human primates have demonstrated that vector-encoded HIV mosaic antigens improve the depth and breadth of cellular immune responses, as well as antibody responses. 38 In particular, mosaic HIV Env vaccines delivered in adenovirus or by modified vaccinia Ankara (MVA), a replication-deficient viral vector, demonstrated a strong protective effect against infection by a subsequent simian human immunodeficiency virus challenge. 39 Currently, a phase-I clinical trial is recruiting participants to assess the safety and tolerability of MVA-HIV Env mosaic vaccine in healthy adult participants.…”
Section: Dealing With Hiv-1 Genetic Diversitymentioning
confidence: 99%